Pemberitaan Kasus Covid-19 di Cnnindonesia.com - Saddam Presiado Illahiwahyu; Tia Muthiah Umar (UNISBA Press, 2022)
Abstract. The emergence of a new variant of the Covid-19 virus named Omicron made Indonesians nervous at the end of 2021. At the beginning of 2022, precisely in January 2022, the number of positive cases of the Omicron variant increased due to the characteristics of the Omicron variant which spread very quickly. Thus, this incident became the main topic of news on various online news portals. CNNIndonesia.com is one of the online news portals that always presents news on the development of the Omicron variant case. In this study, the approach used is qualitative and the critical discourse analysis method of the Teun A. Van Dijk model by selecting news from the online news portal CNNIndonesia.com regarding the increase in cases of the Omicron variant. In this study, the researcher chose the critical paradigm. The results show that in the dimensions of the text structure, CNNIndonesia.com displays more content which includes an affirmation of how much the number of cases of the Omicron variant has increased, and the main cause of the increase in cases. In the dimension of social cognition, journalists use event schemas and person schemas in describing issues regarding the increase in cases of Omicron variants. And on the dimension of social context, the closeness of the owner of PT Trans News Corpora which oversees CNNIndonesia.com with the government affects the direction of the news. Abstrak. Munculnya varian baru dari virus Covid-19 bernama Omicron membuat resah masyarakat Indonesia pada akhir tahun 2021. Pada awal tahun 2022 tepatnya pada bulan Januari 2022, angka kasus positif varian Omicron mengalami peningkatan dikarenakan karakteristik varian Omicron yang sangat cepat menyebar. Sehingga, peristiwa ini menjadi topik utama pemberitaan di berbagai portal berita online. CNNIndonesia.com menjadi salah satu portal berita online yang selalu menghadirkan berita perkembangan kasus varian Omicron tersebut. Di dalam penelitian ini, pendekatan yang digunakan yaitu kualitatif dan metode analisis wacana kritis model Teun A. Van Dijk dengan memilih berita dari portal berita online CNNIndonesia.com mengenai kenaikan kasus varian Omicron. Dalam penelitian ini juga, peneliti memilih paradigma kritis. Hasil penelitian menunjukan pada dimensi struktur teks, CNNIndonesia.com lebih banyak menampilkan isi yang didalamnya berupa penegasan mengenai seberapa banyak jumlah kenaikan kasus varian Omicron, dan penyebab utama dari kenaikan kasus tersebut. Pada dimensi kognisi sosial, wartawan menggunakan skema peristiwa dan skema person dalam menggambarkan persoalan mengenai kenaikan kasus varian Omicron. Dan pada dimensi konteks sosial, kedekatan pemilik PT Trans News Corpora yang menaungi CNNIndonesia.com dengan pemerintah mempengaruhi arah pemberitaan.